PENYELESAIAN PERCERAIAN PERKAWINAN SIRI YANG TELAH DIITSBATKAN BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 (SUATU TINJAUAN YURIDIS) - L, Sudirman (Jurusan Syariah dan Ekonomi Islam Institut Agama Islam Negeri (IAIN) Parepare, 2015)
The regulation of UU No. 1 Tahun 1974 that not only the marriage should be done according to the law of each religion and beliefs, but also requires it to be registrated by PPN. So, if the marriage is not registrated based of the formal yuridis is called nikah sirri that couldnât be proved if there was confict with the law. However, the Compilation of Islamic Law gives room that marriage to be legalized by reason of divorce. When the marriage broke through divorce in a religious court raised some consequence in law including the legal certainly on the status of marriage and children.